Payment for order flow - Parlour, Christine A.; Rajan, Uday (Journal of Financial Economics, 2003)
We develop a dynamic model of price competition in broker and dealer markets. With no payment for order flow, a zero-profit equilibrium exists. With payment for order flow, spreads widen to more than compensate for this payment; hence, there is no equilibrium in which market makers earn zero profits. While brokerage commissions for market orders can fall, the total transactions cost to submitting a market order remains positive. Consumer and social welfare are both lower in any equilibrium with payment for order flow; payment for order flow redistributes payoffs from traders who demand liquidity to those who supply it.